2019
DOI: 10.1155/2019/5743590
|View full text |Cite
|
Sign up to set email alerts
|

Column Efficiency of Fluoride Removal Using Quaternized Palm Kernel Shell (QPKS)

Abstract: In this research, the adsorption potential of quaternized palm kernel shell (QPKS) to remove F− from aqueous solution was investigated using fixed-bed adsorption column. Raw palm kernel shell waste was reacted with 3-chloro-2-hydroxypropyl trimethylammonium chloride (CHMAC) in order to modify the surface charge. The effects of inlet F− concentrations (2–12 mg/l) and QPKS bed height (2–10 cm) with optimum pH (pH = 3) on the breakthrough characteristics of the adsorption system were determined. In the fixed-bed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Various adsorbents have been investigated and reported for the removal of excess fluoride from water in an effective manner. Some of the widely employed adsorbents are La (III)-Al (III)-activated carbon modified by chemical route [ 21 ], biomaterial functionalized cerium nanocomposite [ 22 ], Quaternized Palm Kernel Shell (QPKS) [ 23 ], bone char and activated alumina [ 24 ], bone char [ 25 ], renewable biowaste [ 26 ], MgFe 2 O 4 –chitosan–CaAl nanohybrid [ 27 ], carbon nanotube composite [ 15 ], Neem Oil-Phenolic Resin Treated Bio-sorbent [ 17 ], etc. However, many of these suffer from either time-consuming synthesis procedure, high processing costs, availability of raw materials, or short lifespan, which makes them impractical to be applied in the rift valleys that are essentially impacted by high fluoride concentration in water [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various adsorbents have been investigated and reported for the removal of excess fluoride from water in an effective manner. Some of the widely employed adsorbents are La (III)-Al (III)-activated carbon modified by chemical route [ 21 ], biomaterial functionalized cerium nanocomposite [ 22 ], Quaternized Palm Kernel Shell (QPKS) [ 23 ], bone char and activated alumina [ 24 ], bone char [ 25 ], renewable biowaste [ 26 ], MgFe 2 O 4 –chitosan–CaAl nanohybrid [ 27 ], carbon nanotube composite [ 15 ], Neem Oil-Phenolic Resin Treated Bio-sorbent [ 17 ], etc. However, many of these suffer from either time-consuming synthesis procedure, high processing costs, availability of raw materials, or short lifespan, which makes them impractical to be applied in the rift valleys that are essentially impacted by high fluoride concentration in water [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…This result showed that the adsorption capacity increased with the increase in initial Cd(II) concentration, as the active sites became occupied more easily. The adsorbate ion saturated the adsorbent more easily and reached equilibrium more quickly with the increase in initial influent concentration due to a larger driving force for mass transfer, allowing the transfer process to overcome the mass transfer barriers in the column [26]. Fig.…”
Section: Effects Of Initial Concentration On Adsorption Capacity and ...mentioning
confidence: 99%
“…The raw and synthesized bentonite clay was checked for fluoride adsorption using fixed bed column of a borosilicate tube with ration of internal diameter to height: 0.05. The diameter-to-height ratio of columns was varied between 0.0375 and 1, which was believed to be effective for reactions to occur (Sulaiman et al 2009;Ma et al 2011;Abu Bakar et al 2019) .To prevent the adsorbent from floating, the column was filled with the necessary amount of adsorbent material between two layers of glass wool at the top and bottom ends. Using a peristatic pump, the column was then continuously fed fluoride-contaminated water at a desired volumetric flowrate of 15 mL/min.…”
Section: Experimentation Of Fluoride Adsorptionmentioning
confidence: 99%